2009
DOI: 10.1097/spc.0b013e3283311c6f
|View full text |Cite
|
Sign up to set email alerts
|

An update on promising agents for the treatment of cancer cachexia

Abstract: A number of promising new agents are currently being developed but are not as yet regarded as standard of care. They include: selective COX-2 inhibitors, ghrelin mimetics, oxandrolone, selective androgen receptor modulators (ostarine), olanzapine, anti-IL-6 antibody and an innovative approach of multitargeted combined treatment. The data reported seem to suggest that the most effective treatment for cancer cachexia may be a combination regimen rather than single-agent treatments. This is in keeping with the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…No grade 3 or 4 toxicities were reported. xci COX-2 inhibition is currently one of the more promising areas of CIC research as this medical therapy directly targets the inflammatory APR of CIC and has shown to be well-tolerated with minimal side-effects.…”
Section: Multi-modality Therapymentioning
confidence: 99%
“…No grade 3 or 4 toxicities were reported. xci COX-2 inhibition is currently one of the more promising areas of CIC research as this medical therapy directly targets the inflammatory APR of CIC and has shown to be well-tolerated with minimal side-effects.…”
Section: Multi-modality Therapymentioning
confidence: 99%
“…Rayavarapu et al showed that BTZ significantly improved muscle function and reduced tumor necrosis factor α expression in the skeletal muscle of mice with myositis [12]. Furthermore, the potential use of BTZ in treating cancer cachexia has also been attempted [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Proteolysis-inducing factor (PIF), a glycoprotein secreted by tumors, and substances such as glucocorticoids, angiotensin II, and TNFα can all cause muscle wasting (24). Several new agents, including androgen-receptor modulators and antagonists of inflammatory cytokines that promote muscle breakdown, are currently in clinical development for cancer cachexia treatment (6,24,25).…”
Section: Discussionmentioning
confidence: 99%